COLLOIDAL DISPERSIONS AS A POTENTIAL NASAL DRUG DELIVERY SYSTEM FOR ONDANSETRON HYDROCHLORIDE – IN VITRO AND IN VIVO PROPERTIES - M.Menaka; V.P.Pandey; Smith, A.Anton (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The influence of the particle size of colloidal dispersion on nasal absorption and the localization of Ondansetron hydrochloride in the dispersion have been investigated in rats. Using scanning electron microscopy, it was found that the freeze-drying process, which was used to load Ondansetron hydrochloride into the colloidal dispersions, had a significant impact on the integrity and surface properties of the nasal epithelium in rats. The optimized formulation was analyzed for the sterility by (total bacterial count) and stability study, which proved that the formulation does not contain bacteria and fungi, found to be stable up to 3 years. Pharmacokinetics study was carried out in Wistar rats for Cmax, tmax and AUC, which was found to be 2 h, 0.5 h and 0-2 h respectively. It has been concluded that the tendency of the particle size influence the kinetics of the Ondansetron effect curve. Â  Key words: Nasal spray; Colloidal dispersion; Ondansetron; kinetic study, stability study.